Phonetic Rhythm In Music And Rhythm Correction Training Of Specialized Boarding Schools For Deaf And Hard Of Hearing Students - Ishmatova O. S. (Euro Asian Journal Publishing, 2024)
This article discusses the role of phonetic rhythmicity in music and rhythmic correctional training of specialized boarding schools for deaf and hard-ofhearing students.
Keywords: Phonetic rhythmicity; music and rhythmicity; correction